A Model of Strengthening the Professionalism of Bank Employees - Soehari, Tjiptogoro Dinarjo; Budiningsih, Iffah; Sari, Alvita; Supriyanto, Eko (Advances in Social Sciences Research Journal, 2025)
This study aims to find a model for strengthening the professionalism of Bank employees through human capital, emotional intelligence (EQ), and integrity. The method employed an explanatory quantitative (survey) with the sampling technique used purposive sampling of 44 people from the population of experienced employees/experts about central banks in Indonesia with more than 15 years of work experience. The instruments in this research used questionnaires, and data analysis uses a correlation, and multi-regression The findings of the study are: a) the correlation between human capital, emotional intelligence, and integrity together with the professionalism is positive and very strong (coefficient correlation R2= 0.904); b) human capital, emotional intelligence, and integrity make contribution together to the professionalism of bank employees is 90.40% and the remaining 0.60% by other factors; d) the model of improving professionalism of bank employees is: Y=0.076 + 0.419 X1+ 0, 314 X2 + 0.263 X3 (Y = professionalism; X1= human capital; X2 = emotional intelligence; X3 = integrity); e) the human capital has a higher sensitivity to influence the professionalism than emotional intelligence and integrity. The results of this research have implications that employee professional behavior can be built through strengthening the competence of human resources, emotional intelligence (EQ), and employee integrity.